The biological activity of specific essential oil constituents - Seatlholo, Tsietsi Samuel (My University, 2008)
ABSTRACT Twenty essential oil constituents (EOC′s) from seven structural groups were tested for their antimalarial, antimicrobial (both bacterial and fungal), anti-oxidant, anticholinesterase and toxicity properties. To test for their antimalarial property, the tritiated hypoxanthine incorporation assay was used, while the disc diffusion and minimum inhibitory concentration (MIC) microplate assays were employed for the antimicrobial properties. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) method was used to test the anti-oxidant property and their toxicity profile was assessed with the 3-(4,5-dimethyl-2-thiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) cellular viability assay. The anticholinesterase activity was determined using the thin layer chromatography (TLC) bioautographic method. The EOC´s were found to inhibit the growth of Plasmodium falciparum with IC50 values ranging between 0.9 to 1528.8μM with E- and Z-(±)-nerolidol, (-)-pulegone, (+)-α-pinene and linalyl acetate being the most active. In combination p-cymene (the least active) and E- and Z-(±)-nerolidol (the most active) displayed the most synergistic interaction (ΣFIC = 0.09), with their antimalarial activity comparable to that of the interaction between E- and Z-(±)-nerolidol and quinine (ΣFIC = 0.01). Eugenol had the most favourable safety index and was the only EOC with anti-oxidant activity comparable to vitamin C. Combination studies showed that E- and Z-(±)-nerolidol and (-)-pulegone or quinine, p-cymene and γ-terpinene or (-)-pulegone potentiated each other′s toxicity. The EOC´s inhibited the growth of Gram-positive, Gram-negative bacteria and yeast with MIC values ranging from 1.66 to >238.4mM. When combined, synergism was observed between (+)-β-pinene and carvacrol or γ-terpinene; γ-terpinene and geranyl acetate when tested against Staphylococcus aureus, while (+)-β-pinene and (-)-menthone showed antagonism against C. albicans. The combinations of EOC′s and a standard antimicrobial resulted in synergistic interactions between carvacrol and ciprofloxacin against Bacillus cereus, eugenol and ciprofloxacin against Eschericia coli, carvacrol and amphotericin B against C. albicans. The trans-geraniol and E- and Z-(±)-nerolidol combination demonstrated an additive interaction against B. cereus, while for eugenol and E- and Z-(±)-nerolidol an indifferent interaction against E. coli was noted. These results show that the biological activities of EOC′s can vary when used alone and in combination. They do have the potential to be used as templates for novel drugs and as adjuncts to modern medicines in the combat against drug resistance.
Keywords: essential oil constituents; antimalarial; antimicrobial; anticholinesterase; toxicity; antioxidants